Construction of Multivariate Tight Framelet Packets Associated with Dilation Matrix (Analysis in Theory and Applications, 2017)
In this paper, we present a method for constructing multivariate tight framelet packets associated with an arbitrary dilation matrix using unitary extension principles. We also prove how to construct various tight frames for $L^2(\mathbb{R}^d)$ by replacing some mother framelets.
Keywords: Wavelet; tight frame; framelet packet; matrix dilation; extension principle; Fourier transform.